Toward an understanding of youth in community governance: Policy priorities and research directions - Zeldin, Shepherd (2018)
ABSTRACT: For more than a decade, many researchers and practitioners have endorsed a “positive youth development” approach, which views adolescents as active contributors to their own development and as assets to their communities. As part of this shift, youth are increasingly being invited to engage in community governance. In youth organizations, schools, community organizations, and public policy arenas, youth are making strong contributions to advisory boards and planning councils, and are integrally involved in key day-to-day functions such as program design, budgeting, outreach, public relations, training, and evaluation. State and local policy-makers are also beginning to endorse the engagement of youth in community governance. This policy endorsement, however, has largely occurred independent of scholarship on adolescent development. In this Social Policy Report, our aim is to help bridge this gap. We discuss the cultural context for youth engagement, theoretical rationales and innovative models, empirical evidence, and priorities for policy and research. Why involve youth in community governance? Three main theoretical rationales have been established: Ensuring social justice and youth representation, building civil society, and promoting youth development. Moreover, across the country, innovative models demonstrate that the theory can be effectively translated into policy. Finally, a strong research base supports the practice. When youth are engaged in meaningful decision-making – in families, schools, and youth organizations – research finds clear and consistent developmental benefits for the young people. An emerging body of research shows that organizations and communities also derive benefits when youth are engaged in governance. Several directions need to be pursued for youth engagement to exert a maximum positive impact on young people and their communities. We recommend three 91 areas for policy development. First, public awareness of the practice needs to be better established. Societal expectations for youth remain low and negative stereotypes remain entrenched in the mass media. Second, more stable funding is needed for youth engagement. It will be especially critical to support community-based youth organizations because these places are likely to remain the primary catalysts for youth engagement in the civic life of communities. Third, it is necessary to build local capacity by supporting outreach and training through cross-sector community coalitions and independent, nonprofit intermediary organizations. These entities are best positioned to convince stakeholder groups to chart, implement, and sustain youth engagement. It is equally important to broaden the scientific context for youth engagement in community governance. Priorities for scholars are to focus research on understanding: the organizational and community outcomes that emanate from engaging youth in governance; the competencies that youth bring to governance; and how the practice of youth engagement can be sustained by communities